2019
DOI: 10.1016/j.athoracsur.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Deep Hypothermia With Retrograde Cerebral Perfusion Versus Moderate Hypothermia With Antegrade Cerebral Perfusion for Arch Surgery

Abstract: Background. Patients undergoing aortic arch replacement are at high risk for neurologic injury. This study compared two different established neuroprotective strategies in patients undergoing elective transverse hemiarch replacement. Methods. Twenty patients undergoing hemiarch replacement were prospectively randomized to receive deep hypothermic circulatory arrest with retrograde cerebral perfusion (DHCADRCP) or moderate hypothermic circulatory arrest with antegrade cerebral perfusion (MHCADACP). All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…All patients had formal preoperative and postoperative neurologist examinations and magnetic resonance imaging, which revealed clinically evident stroke rates of 11% and 9%, respectively, and strikingly, the magnetic resonance imaging-proven cerebral infarct rate was 100% in the antegrade group but only 45% in the retrograde group. 3 Interestingly, there was no difference in the relative frequency of right-to left-sided emboli in this well-controlled study. In contradistinction, Kim and colleagues 1 posit that right axillary cannulation will specifically reduce right-sided cerebroembolic phenomena because of the retrograde blood flow pattern down the innominate artery.…”
Section: Thomas G Gleason MDmentioning
confidence: 51%
See 1 more Smart Citation
“…All patients had formal preoperative and postoperative neurologist examinations and magnetic resonance imaging, which revealed clinically evident stroke rates of 11% and 9%, respectively, and strikingly, the magnetic resonance imaging-proven cerebral infarct rate was 100% in the antegrade group but only 45% in the retrograde group. 3 Interestingly, there was no difference in the relative frequency of right-to left-sided emboli in this well-controlled study. In contradistinction, Kim and colleagues 1 posit that right axillary cannulation will specifically reduce right-sided cerebroembolic phenomena because of the retrograde blood flow pattern down the innominate artery.…”
Section: Thomas G Gleason MDmentioning
confidence: 51%
“…To date, there have been five low-volume randomized, controlled trials in human patients and several large database and meta-analyses comparing antegrade cerebral perfusion (most often delivered by right axillary artery cannulation) with retrograde cerebral perfusion, and these studies have generally revealed no difference in stroke and mortality or, especially with respect to stroke, they actually have been in favor of retrograde cerebral perfusion with central cannulation. [3][4][5][6][7][8][9][10] The inclusion of both elective and emergency cases, particularly with only 116 patients in each group, opacifies the issue further. In a study of 264 consecutive acute type A aortic dissection cases, when stratified by cannulation strategy alone, both stroke rate and mortality were significantly lowest with central cannulation, followed by axillary cannulation, then by femoral cannulation.…”
Section: Thomas G Gleason MDmentioning
confidence: 99%
“…Despite no significant difference in clinically evident neurologic injury between patient who had MHCA with ACP and DHCA with RCP patients, the former had a higher incidence of radiographic neurologic injury (n=9,100% vs n=5, 45%; p=0.01). 26 Moreover, an STS database analysis of 7353 patients found that retrograde cerebral perfusion demonstrated a low risk of acute stroke in patients who underwent type A dissection repair. 27 The literature is further obscured by multiple studies advocating one technique over the other.…”
Section: Discussionmentioning
confidence: 99%
“…To the credit of the group at Emory, RCP has been demonstrated to have advantages through the washout phenomenon. 3 Leshnower et al randomized 20 patients to ACP at 26 C compared with RCP at a mean temperature of 20 C. 3 They identified no differences in bypass times, cross-clamp times, of circulatory arrest times between groups. The National Institutes of Health Stroke Scale scores were equivalent across approaches, but when they imaged the patients they saw differences.…”
Section: Cerebral Protection From Nothing To Both Retrograde and Antementioning
confidence: 99%